Bokujinkai: Japanese calligraphy and the postwar avant-garde - Bogdanova-Kummer, Eugenia (Japanese visual culture, 2020)
The Bokujinkai-or 'People of the Ink'-was a group formed in Kyoto in 1952 by five calligraphers, Morita Shiryu, Inoue Yuichi, Eguchi Sogen, Nakamura Bokushi, and Sekiya Yoshimichi. The avant-garde calligraphy movement they launched aspired to raise calligraphy to the same level of international prominence as abstract painting. To realize this vision, the Bokujinkai established creative collaborations with artists from European Art Informel and American Abstract Expressionism, and soon began sharing exhibition spaces with them in New York, Paris, Tokyo, and beyond. By focusing on this exceptional moment in the history of Japanese calligraphy, I show how the Bokujinkai rerouted the trajectory of global abstract art and attuned foreign audiences to calligraphic visualities and narratives